High abundances of cyanomyoviruses in marine ecosystems demonstrate ecological relevance. Issue 2 (2nd January 2013) - Matteson, Audrey R.; Rowe, Janet M.; Ponsero, Alise J.; Pimentel, Tiana M.; Boyd, Philip W.; Wilhelm, Steven W.
Abstract The distribution of cyanomyoviruses was estimated using a quantitative PCR (qPCR) approach that targeted the g20 gene as a proxy for phage. Samples were collected spatially during a > 3000 km transect through the Sargasso Sea and temporally during a gyre‐constrained phytoplankton bloom within the southern Pacific Ocean. Cyanomyovirus abundances were lower in the Sargasso Sea than in the southern Pacific Ocean, ranging from 2.75 × 103 to 5.15 × 104 mL−1 and correlating with the abundance of their potential hosts (Prochlorococcus and Synechococcus). Cyanomyovirus abundance in the southern Pacific Ocean (east of New Zealand) followed Synechococcus host populations in the system: this included a decrease in g20 gene copies (from 4.3 × 105 to 9.6 × 103 mL−1) following the demise of a Synechococcus bloom. When compared with direct counts of viruses, observations suggest that the cyanomyoviruses comprised 0.5 to >25% of the total virus community. We estimated daily lysis rates of 0.2–46% of the standing stock of Synechococcus in the Pacific Ocean compared with c. < 1.0% in the Sargasso Sea. In total, our observations confirm this family of viruses is abundant in marine systems and that they are an important source of cyanobacterial mortality.